Pengaruh Penerapan Digital Entrepreneurship pada Pelaku UMKM Terhadap Peningkatan Penjualan - Fachrurazi Fachrurazi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The importance of conducting this research is further strengthened by data showing that MSMEs that adopt digital technology tend to experience a significant increase in sales compared to those that have not adopted it. This study aims to examine more deeply the effect of digital entrepreneurship implementation on increasing MSME sales. By understanding the factors that influence the success of digitalization, it is hoped that this research can provide appropriate recommendations for MSME players in implementing digital strategies. The research method used in this study is a literature study or literature review. Literature study is a research method that collects, analyzes, and interprets secondary data from various relevant sources. These sources include books, journal articles, research reports, and other reliable sources related to the research topic, namely the effect of implementing "digital entrepreneurship" in MSME players on increasing sales. This study shows that the implementation of digital entrepreneurship has a significant positive impact on increasing sales of MSMEs in Indonesia. Although there are some barriers, the benefits derived from the adoption of digital technology are far greater. Therefore, efforts to encourage the digitalization of MSMEs must continue to be various stakeholders